PERANAN DINAS SOSIAL DALAM PENANGGULANGAN TUNAWISMA DAN PENGEMIS DI SUMATERA UTARA - Bertha Nelya; Jonni Pranatal Sihombing (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) UDA, 2020)
This study aims at finding the role of the social service in overcoming homelessness and papa groups in North Sumatra Province. Qualitative research methods was applied in this research, the results of research that the Social Service has a very important role in the handling of the homeless and destitute groups in the city of Medan, North Sumatra Province. The role of the Social Service is to have carried out a Basic Strategy with problem tracking and assessment, Service and Rehabilitation Implementation, Resocialization phase, and advanced guidance stage. Social Service of North Sumatera Province has a program in carrying out rehabilitation of homeless / homeless and destitute groups. The result is homelessness and the papa / beggars gradually want to be fostered. The rehabilitation program provided by the Provsu Social Service for the homeless / homeless and disadvantaged groups, received a positive response from them. The statements of the five respondents who were rehabilitated explained that they were taught various skills to be independent so that they did not take to the streets again. They are also more motivated to become a better life.